Interface for Data Protection and Integrity in IoT Equipment for Industry - Belu, N.; Ionescu, L.M.; Mazare, A.G. (IOP conference series. Materials Science and Engineering, 2020)
Presently, industrial processes are increasingly based on the equipment that communicates with each other. IoT is present in all branches of the manufacturing process, from the flows of the equipment that work together to achieve the finished product, to the equipment for checking the quality of the process, to the existing logistics infrastructure inside the factory, to the coordination and administration side. One of the problems raised by using IoT is that related to data security and integrity. We are talking about data protection for unauthorized access: maintaining confidentiality at the level of the different departments in the production flow, protecting the data provided by equipment and preventing the injection of unauthorized data flows and we are talking about ensuring data integrity: the data from the equipment must be resistant to any disturbances that occur in the industrial environment on the communication channels (wireless or wired), be assured the correctness of the transmission of the commands from the operator to the equipment. The paper proposes a specialized IoT interface that ensures the protection and integrity of the data transmitted between endpoints. The protection is provided by a light encryption algorithm based on two keys stored at the source and the recipient and on a very simple but efficient coding / decoding scheme. Data integrity is ensured by an 8-bit code word algorithm that allows for the detection of 2 wrong bits and the correction of a wrong bit for a 4-bit packet. All these features are provided by a computer system integrated in the IoT equipment. The efficiency of the solution is illustrated by a case study where in the manufacturing process of pistons it was desired to introduce specific elements Industry 4.0: communication between equipment in order to detect problems in the flow of manufacture (a Poka Yoke system). On the one hand, the system is presented without the protection solution in which there are several communication errors due to the disturbances induced on the communication channels on the other side to the system, the interface proposed in this article is added (at minimum cost) and the performances will be presented in the communication introduced by it.